PENERAPAN PENILAIAN AUTENTIK DALAM PEMBELAJARAN IPAS MELALUI PROYEK PENGAMATAN FOTOSINTESIS - Elsa Wulan Cahyani; Yuni Pantiwati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study describes the implementation of authentic assessment in Science and Social Studies (IPAS) learning through a photosynthesis observation project for fourth-grade students at SD Muhammadiyah 1 Kota Malang. Authentic assessment was carried out by evaluating students’ attitudes, knowledge, and skills comprehensively through direct observation of learning processes and outcomes that are relevant to real-life contexts. The results showed that the implementation of authentic assessment was effective in improving students' understanding of the photosynthesis concept, which is often considered abstract, as well as in developing scientific skills and positive attitudes. Challenges encountered included time constraints and large class sizes, indicating the need for classroom management support and teacher training to optimize the implementation of authentic assessment. These findings reinforce the importance of authentic assessment as a holistic and contextual evaluation strategy in IPAS learning at the elementary school level.